2020
DOI: 10.1021/acs.bioconjchem.0c00365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Code Expansion Enables Site-Specific PEGylation of a Human Growth Hormone Receptor Antagonist through Click Chemistry

Abstract: Regulation of human growth hormone (GH) signaling has important applications in the remediation of several diseases including acromegaly and cancer. Growth hormone receptor (GHR) antagonists currently provide the most effective means for suppression of GH signaling. However, these small 22 kDa recombinantly engineered GH analogs exhibit short plasma circulation times. To improve clinical viability, between 4-6 molecules of 5 kDa poly(ethylene glycol) (PEG) are nonspecifically conjugated to the 9 amines of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 64 publications
(144 reference statements)
0
18
0
Order By: Relevance
“…PEGylation was first introduced by Abuchowski and co-workers in 1977 and describes the covalent conjugation of one or multiple poly­(ethylene glycol) (PEG) chains to a protein in a random or site-specific manner, being already exploited to a large number of biomolecules. , The resulting PEG-protein conjugates exhibit longer circulation time, mainly due to diminished renal clearance and shielding of immunogenic protein epitopes, preventing fast depletion from the bloodstream. Within the last few years, PEG’s image as being a safe and nonimmunogenic polymer, however, has been challenged by numerous reports on the occurrence of anti-PEG antibodies ,, in clinic, diminishing the benefits of PEGylation, thereby compromising its therapeutic efficacy. , Therefore, manifold efforts to find alternative polymer platforms for protein conjugation, covering synthetic as well as biodegradable, natural polymer systems, have been made. , …”
Section: Introductionmentioning
confidence: 99%
“…PEGylation was first introduced by Abuchowski and co-workers in 1977 and describes the covalent conjugation of one or multiple poly­(ethylene glycol) (PEG) chains to a protein in a random or site-specific manner, being already exploited to a large number of biomolecules. , The resulting PEG-protein conjugates exhibit longer circulation time, mainly due to diminished renal clearance and shielding of immunogenic protein epitopes, preventing fast depletion from the bloodstream. Within the last few years, PEG’s image as being a safe and nonimmunogenic polymer, however, has been challenged by numerous reports on the occurrence of anti-PEG antibodies ,, in clinic, diminishing the benefits of PEGylation, thereby compromising its therapeutic efficacy. , Therefore, manifold efforts to find alternative polymer platforms for protein conjugation, covering synthetic as well as biodegradable, natural polymer systems, have been made. , …”
Section: Introductionmentioning
confidence: 99%
“…Conjugation of a 20 or 40 kDa PEG to the N-terminal of B2036 resulted in approximately 2- and 17-fold reduction in receptor binding activity, respectively . In addition, we have previously incorporated an unnatural amino acid into B2036 at amino acid Y35 for site-specific PEGylation using copper-catalyzed click chemistry and reported that 20 kDa PEG-conjugated B2036 exhibited 5.8-fold reduction in bioactivity compared to a 72.8-fold reduction observed for pegvisomant . Using this approach led to a conjugation efficiency of 90%.…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, we have previously incorporated an unnatural amino acid into B2036 at amino acid Y35 for site-specific PEGylation using coppercatalyzed click chemistry and reported that 20 kDa PEGconjugated B2036 exhibited 5.8-fold reduction in bioactivity compared to a 72.8-fold reduction observed for pegvisomant. 25 Using this approach led to a conjugation efficiency of 90%. However, the incorporation of an unnatural amino acid into B2036 reduced the protein expression yield and a byproduct (truncated protein) caused by the amber code requires additional purification steps to remove.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic 9 and affinity-guided tagging 10 provide effective selectivity, while genetic code expansion offers the unique opportunity to incorporate the orthogonal handles during protein biosynthesis. 11 The use of bioorthogonal catalysis coupled with DNA nanostructures is a particularly intriguing new direction to site-selectively modify proteins. 12 Bioorthogonal functionalization is an enabling technology for a broad range of applications.…”
mentioning
confidence: 99%